EFFETS DU TRAVAIL DU SOL SUR LE COMPORTEMENT PHYSIQUE ET BIOLOGIQUE D’UN SOL SOUS UNE CULTURE DE LENTILLE (LENS EXCULENTA) DANS LA RÉGION DE TIARET ALGÉRIE - Nadia, Bouchenafa; Oulbachir, K; Kouadria, M (European Scientific Journal, ESJ, 2014)
Soil management practices influence soilphysical and chemicalcharacteristics and bring about changes in the soilmicrobialcommunity structure and function. In thisstudy, the effects of conventional and no-tillage practices on microbialcommunity structure, selectedphysicochemicalpropertiesweredetermined in a continuous corn system on a silt loamsoil. The no-tillage treatmentresulted in highersoilcarbon and nitrogen contents, viable microbialbiomass, at the 0– 25 cm depththan the conventional tillage treatment. Soilmicrobialcommunity structure assessed,using indicative of fungi, bacteria, in the no-till surface soil. Results of principal components analysisbased on soilphysicochemical in agreement. Theseresultsindicatethat tillage practice and soildepthweretwo important factorsaffectingsoilmicrobialcommunity structure and activity, and conservation tillage practices improvebothphysicochemical and microbiologicalproperties of soil.